Medium-chain-length poly-3-hydroxyalkanoates-carbon nanotubes composite as proton exchange membrane in microbial fuel cell - Yusuf, Hindatu; Annuar, Mohamad Suffian Mohamad; Syed Mohamed, Syed Mohammad Daniel; Ramesh, Subramaniam (Taylor & Francis, 2019)
Medium-chain-length poly-3-hydroxyalkanoates (PHA) and carboxyl group-functionalized multiwalled carbon nanotubes (MC) were used to fabricate a composite membrane for application in a double-chambered microbial fuel cell (MFC). MC was composited into PHA at 5%, 10%, and 20% w/w via ultrasound dispersion blending method. PHA-MC composite was compared with Nafion 117 as proton exchange membrane in MFC operated with palm oil mill effluent (POME) wastewater. The composite exhibited prerequisite separator membrane characteristics. The dispersion of MC in the polymer matrix increased its interfacial surface area and water uptake properties. PHA-MC10% membrane in MFC showed maximum power density of 361 mW/m 2 , which was comparable with Nafion 117 (372 mW/m 2 ). Internal resistance decrease, chemical oxygen demand (COD) removal, coulombic efficiency (CE), and conductivity of the PHA-MC10% were superior to Nafion 117. The environmental-friendly material could provide an alternative towards realizing practical MFC application.